Oil Price and Banking Sectors in Gulf Cooperation Council Economies before and after the Global Financial Turmoil: Descriptive Analysis - Saif-Alyousfi, Abdulazeez Y.H.; Md-Rus, Rohani; Mohd, Kamarun Nisham Taufil (International Journal of Energy Economics and Policy, 2018)
In this paper, we analyze the evolution of the banking sector in the six GCC countries including concentration, trends in credit growth, balance sheets, and financial safety as well as oil price over the period 2000-2014. In general, our analysis finds that the level of capitalization of banks in GCC countries appears comfortable despite the adverse effect of the financial crisis. Despite apparent financial soundness, there are certain weaknesses in the banking sector of GCC countries which needs investigation. Firstly, GCC countries have registered sharp growth in of credit in consonance with the steady rise in the price of oil straining the liquidity position of banks. Secondly, some banking systems in GCC countries are highly exposed to households secured by their salaries especially in Bahrain (50 to 60%) and Qatar 70%). Thirdly, although the overall NPLs ratio in the GCC banking sector is at historically low levels, however, it has remained high when compared to the average NPLs ratio of the global banks. Finally, we find that banks in GCC countries seem to keep low levels of liquidity compared to international standards. Keywords: Oil price, Banking sector, Credit growth, Financial statements, Financial soundness, Global Financial Crisis, GCC countries JEL Classifications: G20, G21, C23, L2 DOI: https://doi.org/10.32479/ijeep.7074